PENGARUH GESEKAN MATERIAL RAW MIX PENYEBAB KEAUSAN TERHADAP VERTICAL MILL PADA TYRE VERTICAL MILL - Darmadi, Herry; Gultom, Golfrid; Mustakim, Mustakim; Kurnia, Dian; Husainy, Husainy; Syabil, Irfan (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
Vertical roller mill is a combination of the system on millstone and rocker arm, in the process the millstone is driven by a motor so that it can rotate, the material enters through the middle of the millstone, with the centrifugal force the material above the millstone is ground by a roller which is pressured by a hydraulic cylinder. Tyre I experienced the largest wear rate with a total wear rate of 46,79 gr/hour, Tyre II experienced a wear rate of 38,58 gr/hour, Tyre III experienced a wear rate of 31,74 gr/hour, and the smallest Tyre IV experienced a wear rate of 24,90 gr /hour. And maintenance is done on the main components of the vertical mill so that the raw mix material can be processed properly.